Experienced workplace incivility: developing emotional exhaustion as a mediator and its consequences among millennial employees - Reny Yuniasanti,; Nurul Ain Hidayah Abas,; Hazalizah Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Incivility is a silent disruption and a contemporary workplace crisis which commonly occurs in an organization. Experience of workplace incivility is defined as the frequency of experience of low intensity by employee in relation to deviant workplace behavior with ambiguous intention to the target of the violation of workplace norms with mutual consideration. Most studies on workplace incivility have shown that occurrence of workplace incivility has negative consequences for both individual employees and the whole organization. The mediator between workplace incivility and work consequences has to be explored and investigated to more understand their correlation. Using the affective event theory will predict significantly emotional exhaustion mediate the relationship between experienced of workplace incivility to turnover intention and psychological well-being. Research about experience of workplace incivility and its consequences need to be explored and adapted with millennial employees who are the back bone of organization in the future.